Bromodomain and extra-terminal proteins in solid tumors: regulators of immune microenvironment and emerging therapeutic targets - Sharma, Deeksha; Bushnell, Grace G.; Kalman, Alexander P.; Hutchens, Chloe M.; Burness, Monika L. (Frontiers in Immunology, 2026)
Bromodomain and Extra-Terminal domain (BET) proteins are key epigenetic readers that recognize and bind acetylated lysine residues on histones, orchestrating transcriptional programs that drive oncogenic processes. BET proteins regulate the expression of oncogenes involved in proliferation, survival, and differentiation, thereby promoting tumor initiation, progression, and therapy resistance across a wide range of solid tumors. Recent findings implicate BET proteins in maintaining cancer stem cells (CSCs), a subpopulation of tumor cells characterized with self-renewal capacity, plasticity, and the ability to evade conventional therapies. In CSCs, BET proteins coordinate stemness-associated transcriptional networks, and drive tumor persistence, metastasis, and relapse following treatment. BET proteins also shape the tumor immune microenvironment by modulating the expression of key immune checkpoint molecules such as PD-L1, regulating cytokine production, and controlling antigen presentation, which collectively influence adaptive and innate immune responses. BET inhibition enhances T cell infiltration and activation while suppressing the immunosuppressive functions of tumor-associated macrophages. The dual role of BET proteins in controlling both stemness and immune regulation positions them as central regulators of tumor-intrinsic and immune-mediated mechanisms in cancer. This makes BET proteins attractive therapeutic targets, as their inhibition offers the potential to simultaneously suppress tumor growth and reprogram the immune microenvironment. Preclinical and early clinical studies demonstrate that combining BET inhibitors with chemotherapy, targeted therapies, or immune checkpoint blockade synergizes anti-tumor responses. Future research focused on understanding the context-specific functions of BET proteins, and optimizing combination strategies will be critical to fully harness their therapeutic potential in solid tumors.